Prevalence of suicidal thoughts and factors affecting it in pregnant women, 2022 - Malihe Darvishi; Mahin Tatari; Rahman Bardi Ozouni-Davaji; Fatemeh Seifi (Mashhad University of Medical Sciences, 2024)
Introduction: Suicidal thought is an important predictive factor for committing suicide. One of the causes of the death of pregnant women is attempting suicide, so identifying its risk factors can be effective on policies aimed at reducing this problem. Therefore, the present study was conducted with aim to investigate the prevalence of suicidal thoughts and the factors influencing it in pregnant women. Methods: A cross-sectional study with a descriptive-analytical approach was conducted through a census in 2022 on 515 pregnant women under the care of 10 urban comprehensive health service centers in Aliabad Katoul city. The Persian version of Beck's Suicide Ideation Scale, the Persian version of the Goldberg General Health Questionnaire, and the HITS domestic violence screening form were the study tools. Using these instruments, the prevalence of suicidal thoughts and its relationship with mental health, physical health, domestic violence, sleep disorders, anxiety, and depression was examined. Data analysis was performed using SPSS statistical software (version 23) and included Spearman correlation, Chi-square tests, Fisher's exact test, and multiple logistic regressions. A p-value of less than 0.05 was considered significant. Results: The prevalence of suicidal ideation was 7.9%. The level of suicidal ideation of pregnant women was low. Mental health of pregnant women was in the category of morbid symptoms. Age less than 25 years old, unwanted pregnancy, pregnancy more than 4 times, childbirth more than 4 times, having 4 or more children and high risk behavior of the spouse showed a statistically significant relationship with suicidal ideation (p=0.05). Conclusion: Considering the low mental health of pregnant women, there is a need for planning to carry out necessary interventions and continuous screenings of pregnant women in order to promote and ensure the mental health of pregnant women, especially women suffering from domestic violence.